Explaining conversations : a developmental social exchange theory - Thomas, R. Murray (Robert Murray), 1921-2016 (Jason Aronson, 2012)
Explaining Conversations offers a different way of interpreting people's social exchanges than has been available in the past. The book is replete with examples of people's verbal interactions in the form of chats, arguments, debates, and negotiations, both within a culture and across cultures. The volume's subtitle, A Developmental Social-Exchange Theory, identifies a theme featured in Chapters 2 and 5-the typical pattern by which social-exchan.